Comparisons of digestive enzyme activities and gut performance post feeding with different protein sources between 2g- and 5g-shrimp, Penaeus vannamei - Kasamechotchung, Chanadda; Plaipetch, Pichet; Munkongwongsiri, Natthinee; Kruangkum, Thanapong; Sritunyalucksana, Kallaya; Khidprasert, Siriwan (Food Agricultural Sciences and Technology, 2024)
The objective of this study is to compare digestive enzyme activities between 2 g-shrimp and 5g-shrimp fed with similar diet. Also, it is extended to compare the gut performance including gut passage time (GPT), gut retention time (GRT), gut passage rate (GPR) after feeding with diets of different protein sources. The activities of three digestive enzymes in digestive organs including stomach, hepatopancreas and intestine in the 2 g-shrimp and 5 g-shrimp were compared. Overall, the activities of trypsin, lipase and amylase were found to be higher in the 5 g-shrimp than those of 2 g-shrimp in all three organs tested. In addition, there was no trypsin and lipase activities detected in the intestine of the 2 g-shrimp. The level of lipase activity in the stomach of 2 g-shrimp was 8-times lower than those of the 5 g-shrimp. The feeding experiment was performed to compare the efficiencies of the gut performance in the 2 g-shrimp and 5g-shrimp post feeding with the diets containing different protein sources. Three diet formulae that varied in proportion of fish meal (FM) and soybean meal (SBM) including F1 (30% FM), F2 (10% FM + 28% SBM), and F3 (42% SBM) to result in acceptable total crude protein contents for penaeid shrimp ranging 37% were prepared. The gut performance indicators include gut passage time (GPT), gut retention time (GRT), and gut passage rate (GPR). There were no significant differences among gut performance indicators of the 5 g-shrimp fed with 3 different diets. In contrast, the 2 g-shrimp fed with F3 demonstrated highest GPT, GRT and those fed with F1 revealed highest GPR. Taken together, the results suggest that the digestive functions of the 2 g-shrimp are underdeveloped and the SBM diet retained longer and moved with slow rate in the digestive tract. Further study to demonstrate the adaptability of the 2 g-shrimp to different feed if shrimp has been fed for a long time.